Photobiomodulation Therapy and Dental-derived Mesenchymal Stem Cells: a Review of Literature - Vahdatinia, Farshid; Fekrazad, Reza (Regeneration, Reconstruction & Restoration (Triple R), 2020)
Introduction: The role of PBMT in regulating cellular activity as well as its biostimulation effect on cell proliferation or inhibition has led a group of studies to investigate its effect on stem cells. The aim of this review study was to investigate the effect of photobiomodulation therapy (PBMT) on the function of Dental Derived Mesenchymal Stem Cells (DDMSCs). Materials and Methods: The study was done by reviewing laboratory and clinical studies conducted until 2020 according to the following keywords: Photobiomodulation therapy, Low Level Laser Therapy, Regeneration, Dental Derived Mesenchymal Stem Cells using “and” conjunction in Pub med, Medline, Springer, Elsevier, and Science direct databases. Results: The findings of 9 related articles indicated the role of PBMT in improving proliferation and viability of DDMSCs. Also, the functional improvement of stem cells in the regeneration of dental pulp can be one of the most crucial effects of PBMT. Conclusion: In general, the most important finding of this study was the positive effect of PBMT in proliferation and differentiation of Mesenchymal stem cells (MSCs). However, the insufficient clinical trials remain an obstacle in achieving definitive results in examining the relationship between PBMT and MSCs.